Fat Intake Reduction Strategies among Children and Adults to Eliminate Obesity and Non-Communicable Diseases in the Eastern Mediterranean Region - Ayoub Al Jawaldeh; Hanin Al-Jawaldeh (MDPI AG, 2018)
Non-communicable diseases (NCDs) are the leading cause of mortality globally with an estimated 39.5 million deaths per year (72% of total death) in 2016, due to the four major NCDs: cardiovascular diseases, cancers, chronic respiratory diseases and diabetes. In the Eastern Mediterranean Region (EMR), almost 68% of all deaths are attributed to NCDs commonly known as chronic or lifestyle-related diseases. Two-thirds of NCD premature deaths are linked to 4 shared modifiable behavioral risk factors: tobacco use, unhealthy diet, physical inactivity and harmful use of alcohol. These unhealthy behaviours lead to 4 key metabolic/biological changes; raised blood pressure, overweight/obesity, high blood glucose levels/diabetes, and hyperlipidemia (high levels of fat in the blood), that increase the risk of NCDs. Globally, countries are already working towards agreed global goals on maternal and infant nutrition and on the prevention of NCDs. In both fields the goals include halting the increase in overweight and obesity and reducing NCD diet-related risk factors including reducing saturated fatty acids (SFAs) and trans fatty acids (TFAs) intake. The objective of this review is to present an up-to-date overview of the current fat (SFAs and TFAs) intake reduction initiatives in countries of the Eastern Mediterranean Region (EMR) by highlighting national and regional programs, strategies and activities aiming at decreasing the intakes of dietary fat (SFA and TFA). The literature review shows that the average intake of SFA is estimated to be 10.3% of the total energy intake (EI), exceeding the WHO (World Health Organization) upper limit of 10%. The average TFA intake is estimated at 1.9% EI, which also exceeds the WHO upper limit of 1% EI. The highest SFAs intake was reported from Djibouti, Kuwait, Saudi-Arabia, Lebanon and Yemen, while the highest TFAs intakes were reported from Egypt and Pakistan. If countries of the EMR receive immediate public health attention, that toll of NCD-related morbidity and mortality would be considerably decreased through the implantation of evidence-based preventive interventions. In this context, reductions in SFAs and TFAs intakes have been highlighted as cost-effectives strategies that may hamper the growth of the NCD epidemic.